USING INTERACTIVE METHODS IN IMPROVING SPELLING LITERACY - Amirkulova Zebuniso Mustafakulovna; Quvonova Jasmina Absaxatovna (Bright Mind Publishing, 2025)
This article shows the features of the use of innovative technologies used in the study of speech sounds in literacy classes in primary grades.
Keywords: Phonetics, interactive methods, initial adjectives, Venn diagram, FSMU, BBB technology.